Electrospun Conductive Nanofiber Yarn for a Wearable Yarn Supercapacitor with High Volumetric Energy Density - Sun, Xianqiang (Materials (Basel), 2019)
One-dimensional, flexible yarn-shaped supercapacitors for woven cloth have the potential for use in different kinds of wearable devices. Nevertheless, the challenge that supercapacitors face is low energy density. In this paper, we present a low-cost and large-scale manufacturing method to construct a supercapacitor yarn with high power and high energy density. To construct the novel and flexible poly(3,4-ethylenedioxythiophene): poly(styrenesulfonate)–polyacrylonitrile (PDEOT: PSS-PAN)/Ni cotton (PNF/NiC) capacitor yarn, an electrospinning technique was initially used to wrap the polyacrylonitrile (PAN) nanofibers around the core Ni-coated yarn. The PEDOT: PSS–PAN nanofiber composite electrode was created using in situ deposition and H(3)PO(4)/PVA was used as a gel electrolyte. This electrode material has a yarn/nanofiber/PEDOT: PSS nanoparticle hierarchical structure, providing a high specific area and enhanced pseudocapacitance. The electrode demonstrated a high volumetric capacitance of 26.88 F·cm(−3) (at 0.08 A·cm(−3)), an energy density of 9.56 mWh·cm(−3), and a power density of 830 mW·cm(−3). In addition, the PNF/NiC capacitor yarns are lightweight, highly flexible, resistant to bending fatigue, can be connected in series or parallel, and may be suitable for a variety of wearable electronic products.